101 SKILLS YOU NEED TO SURVIVE IN THE WOODS : The Most Effective Wilderness Know-How on Fire-Making, Knife Work, Navigation, Shelter, Food and More - Estela, Kevin (Page Street Publishing Co., 2019)
“Feeder” mind-set means being in control of a situation, proactive rather than reactive. It is an optimistic outlook that reframes any situation as a learning experience. Kevin Estela teaches survival skills from this feeder-based perspective, which is what separates his teaching style from other wilderness instructors. Kevin has written the quintessential guide for an outdoor enthusiast’s “bucket list” of skills―how to make a fire, build a shelter, gather food, find water, use a knife correctly and make cordage. These skills will keep you safe and better prepare you to deal with emergencies in the field, when you’ll need the additional skills of signaling and communication, navigation and crisis first aid taught in this book. Each chapter concludes with more advanced techniques to build your skills in various challenging situations, with tips that even seasoned survival enthusiasts haven’t thought of. 101 Skills You Need to Survive in the Woods is not a onetime read but a lifetime reference you will turn to over and over again. It will become the first thing you pack for any adventure and just might save your― or someone else’s―life.